COVID 19 lock-down measures on Zimbabwean populace - Gumbo, Olivia (Advances in Social Sciences Research Journal, 2020)
This paper examines the impact of COVID-19 lockdown measures on Zimbabwean populace. The objectives of the paper were to understand the influence of lockdown measures on people living in Zimbabwe. The use of virtual qualitative methodology was utilised. The data gathering methods that were used are phone short message services, WhatsApp, telephone conversations with participants, virtual meetings with key informants and informal talks with some participants on shopping queues. The results of the study are that COVID-19 lockdown measures had negative impact on livelihoods of citizens, brought uncertainties on youths’ future, confusion to school students and erosion of social movements. The paper concludes that COVID-19 lock down measures impacted the general public negatively more than the disease itself. It is recommended that the Zimbabwean government considers the impact of lock down restrictions on the most affected groups such as women, youths and children. The government should cushion the vulnerable groups with safety net allowances and consult them when developing strategies that can help them to come out of the shocks they are currently experiencing.